Modelling and Prevention of Acute Kidney Injury through Ischemia and Reperfusion in a Combined Human Renal Proximal Tubule/Blood Vessel-on-a-Chip. Issue 2 (24th February 2022) - Vormann, Marianne K.; Tool, Laura M.; Ohbuchi, Masato; Gijzen, Linda; van Vught, Remko; Hankemeier, Thomas; Kiyonaga, Fumiko; Kawabe, Tetsuhiro; Goto, Takayuki; Fujimori, Akira; Vulto, Paul; Lanz, Henriette L.; et al.
Key Points: We set up an in vitro proximal tubule model that can capture acute kidney damage after an ischemic event. We showed the renoprotective effect of adenosine in an in vitro AKI/rIRI on-a-chip model. We showed a robust model for AKI/rIRI that can be used for high-throughput testing. Visual Abstract: Abstract : Background: Renal ischemia/reperfusion injury (rIRI) is one of the major causes of AKI. Although animal models are suitable for investigating systemic symptoms of AKI, they are limited in translatability. Human in vitro models are crucial in giving mechanistic insights into rIRI; however, they miss out on crucial aspects such as reperfusion injury and the multitissue aspect of AKI. Methods: We advanced the current renal proximal tubule-on-a-chip model to a coculture model with a perfused endothelial vessel separated by an extracellular matrix. The coculture was characterized for its three-dimensional structure, protein expression, and response to nephrotoxins. Then, rIRI was captured through control of oxygen levels, nutrient availability, and perfusion flow settings. Injury was quantified through morphologic assessment, caspase-3/7 activation, and cell viability. Results: The combination of low oxygen, reduced glucose, and interrupted flow was potent to disturb the proximal tubules. This effect was strongly amplified upon reperfusion. Endothelial vessels were less sensitive to the ischemia–reperfusion parameters. Adenosine treatment showed a protective effect on the disruption of the epithelium and on the caspase-3/7 activation. Conclusions: A human in vitro rIRI model was developed using a coculture of a proximal tubule and blood vessel on-a-chip, which was used to characterize the renoprotective effect of adenosine. The robustness of the model and assays in combination with the throughput of the platform make it ideal to advance pathophysiological research and enable the development of novel therapeutic modalities.